ANALISIS NERACA AIR IRIGASI UNTUK TANAMAN PADI PADA SUBAK JAKA SEBAGAI SUBAK NATAK TIYIS - I Putu Riadi Handika; Sumiyati Sumiyati; I Made Anom. S. Wijaya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2015)
Water source of Subak Natak Tiyis irrigation system comes from the upstream of subak drainage water. Those condition was causing uncertainly irrigation water balance in Subak Natak Tiyis, thus it requires further research to determine appropriate irrigation water balance according to the availabilitiy and requirement of irrigation water in Subak Natak Tiyis. The purposes of this research were to analyze the availabilities and requirement of irrigation water of Subak Jaka as Subak Natak Tiyis and determine the water balance irrigation in the Subak Jaka as Subak Natak Tiyis. The analysis of discharge availabilities was carried out by measuring discharge at inlet Subak Jaka. Irrigation water requirement was analyzed using CROPWAT 8.0 software. irrigation water balance was obtained by comparing the discharge of irrigation water was availabilitis and irrigation water requirement so get irrigation water deficit on Subak Jaka. The analysis of discharge availabilities showed high discharge occur at rainy season that was 115.72 liter/second within a year. The smallest discharge occurs in dry season that was 19.01 liter/second within a year. Irrigation water requirement in MT I and MT II average required discharge ranged from 11.0 to 98.5 liter/second for 15 days. The result of irrigation water balance the Subak Jaka occurrence irrigation water deficit three period that was 35.2 liter/second on period June I that highest for 15 days, 16.8 liter/second on period June II and 30.7 liter/second on January I that highest for 15 days.